Human Resource Development Strategy for Cacao Industri Union in West Sumatera (Institut Teknologi Indonesia, 2014)
As the third largest producer of cocoa beans in the world, Indonesia still has many weaknesses to build cocoa industry such as human resources and institutional. Both of these factors cause the cocoa industry was not able to compete in the global market, so the development of cacao industry is said not optimal. The purpose of this paper is to help the government solve the problem. By using the strategy analysis and AHP method hopefully could provide sharper problems identification and also alternative solutions for competitiveness enhancement of Indonesian cocoa industry especially at West Sumatera. This study show that the strategy to increase human resource management is in a union as effort to improve agribusiness empowerment especially at manager self-development particularly at effective working and strategic thinking, whereas the policy on improving the management system and the organization is a top priority.